Impact of Time Pressure Mediation on Perceived Value and Purchase Intention - Septian, Yudha Alvin; Abadi, Ferryal (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study examines the influence of Time Pressure on sales, focusing on its complex interaction with Perceived Value and Purchase Intention, moderated by Brand Image and Product Involvement. Previous research often analyzes these variables independently, leaving a gap in understanding their combined effects. This study bridges that gap by investigating how Time Pressure mediates the relationship between Perceived Value and Purchase Intention, considering the moderating roles of Brand Image and Product Involvement. Using a quantitative approach, data were collected via an online survey of respondents aged 21-55 years with online shopping experience. The Structural Equation Model (SEM) method was applied using SMARTPLS 4 software. Results indicate that Time Pressure significantly influences consumers’ purchasing decisions by increasing the urgency to choose specific products, enhancing Purchase Intention. Brand Image, Perceived Value, Product Involvement, and Time Pressure together explain variations in Purchase Intention. The findings confirm a significant and positive relationship between Perceived Value and Purchase Intention. Additionally, Time Pressure mediates this relationship by creating a sense of urgency, accelerating purchase decisions but potentially increasing regret. These insights highlight the critical role of Time Pressure in shaping consumer behavior in online shopping contexts